Dew Studies under Forest Plantations at New Forest, Dehra Dun - Dabral, B. G.; Bali, H. K.; Bhalla, H. K. L. (Indian Forester, 1964)
The studies discussed here reflect upon the trend of dew deposition inside the chirpine, teak and bamboo plantations growing at F.R.I. Reserve forest. It was observed that dew deposition was much retarded under canopy covers. It was also noticed that no frost was recorded inside these plantations.